The Benefits of Spatially Differentiated Regulation: The Response to Acid Rain by U.S. States Prior to the Acid Rain Program. (12th November 2013) - Perino, Grischa; Talavera, Olena
Abstract: Location is a crucial driver of both the marginal abatement and damage costs of sulfur dioxide emissions by U.S. coal‐fired power plants. Before the start of the Acid Rain Program in 1995, old boilers were subject to emission rate standards set by individual states. We investigate how individual states adjusted their sulfur regulation laws in response to acid rain, and whether they accounted for differences in marginal abatement costs, vulnerability to agricultural damages, special industry interests, or inter‐state externalities. The welfare gain compared to a uniform reduction in emission rate standards is estimated to be $21 million (in 1995 dollars) annually.